HUBUNGAN KEPEMIMPINAN MANAJERIAL KEPALA SEKOLAH DENGAN INOVASI SEKOLAH DI SDN SE KECAMATAN LUWUK UTARA - ARMIN HALUTI (JURNAL PENDIDIKAN GLASSER, 2017)
AbstractThe purpose of this study is to describe the relationship between the vice Principal’s managerial leadership and school innovation in State Elementary School in North Luwuk district. The population of this study is all of the teachers of State Elementary School in North Luwuk, Banggai Regency. This study was used random sampling technique. The total numbers of the sample are 80 teachers. This study was quantitative approach with used correlational design. While the technique of analyzing data used regression technique (regression analysis). Based on the normality tested of the data, it can be described that the a value = 67.975 and b = 0,378 with input the a value and b value into the similar regression, it is reached the simple similar regression where Y = 67.957+ 0,378 X. It means that, the more good of the vice principal’s managerial leadership will probably increase the school innovation. While the vice principal’s managerial leadership with school innovation has positive and significant relationship as big as 67.95%. The suggestion of this study is to increase the school innovation, and the vice principal’s is suggested to think and formulate the purpose and the act of the program, compile and coordinate the human resources and the material resources of the school. Because, the successful of school very depends on the ability to arrange and engage any sources to reach the purpose. The vice principal’s has ability to lead and affect all of the human resources to accomplish the essential of any jobs, and control the management of the school.Key word: Managereial, and Innovation.